2021
DOI: 10.3390/nu13082697
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Melanogenesis-Associated Signaling Pathways Regulated by Argan Press Cake in B16 Melanoma Cells

Abstract: The beneficial effect on health of argan oil is recognized worldwide. We have previously reported that the cake that remains after argan oil extraction (argan press-cake or APC) inhibits melanogenesis in B16 melanoma cells in a time-dependent manner without cytotoxicity. In this study, the global gene expression profile of B16 melanoma cells treated with APC extract was determined in order to gain an understanding of the possible mechanisms of action of APC. The results suggest that APC extract inhibits melani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…These results indicate that the whitening mechanisms of the tested cosmetic are complicated, 46 , 47 likely contributing to the inhibition of melanin expression and transport, as well as preventing pigmentation. Similar mechanisms have been inferred in previous cosmetics ingredient studies; for example, some natural ingredients, such as α-arbutin 48 and resveratrol 49 have been shown to decrease TYR activity to reduce melanin production, while Argan Press Cake (APC) 50 and nicotinamide 51 inhibited melanin transport.…”
Section: Resultssupporting
confidence: 77%
“…These results indicate that the whitening mechanisms of the tested cosmetic are complicated, 46 , 47 likely contributing to the inhibition of melanin expression and transport, as well as preventing pigmentation. Similar mechanisms have been inferred in previous cosmetics ingredient studies; for example, some natural ingredients, such as α-arbutin 48 and resveratrol 49 have been shown to decrease TYR activity to reduce melanin production, while Argan Press Cake (APC) 50 and nicotinamide 51 inhibited melanin transport.…”
Section: Resultssupporting
confidence: 77%
“…Although argan seed cake has been used so far almost exclusively to feed animals [ 12 ], it has also been proposed as a natural exfoliant and moisturizer for use as an ingredient in commercial shampoo and in creams to topically treat sprains, or scabies, and for healing wounds. In particular, recent results suggest that argan seed cake has melanogenesis regulatory effects, and that its ethanol extract might be used as a component of natural whitening products and as pharmacological agent for the treatment of hyperpigmentation disorders [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though argan seed cake has primarily been used for animal feed ( Cherki et al, 2006 ), it has also been suggested as a natural moisturizer and exfoliator for use in commercial shampoos and lotions to heal wounds, sprains, and scabies topically. Recent studies show that the ethanol extract of argan seed cake may be utilized as a natural lightening and pharmacological therapy for treating hyperpigmentation issues because of its effects on melanogenesis ( Bourhim et al, 2018 ; Bourhim et al, 2021 ; ZeinEldin et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%